Effect of body condition score loss during the transition period on metabolism, milk yield and health in Holstein cows - Sun Rui; Jiang Xuejie; Hao Yu; Li Ying; Bai Yunlong; Xia Cheng; Song Yuxi (Journal of Veterinary Research)
This study aimed to investigate the impact of perinatal body condition score (BCS) and its subsequent loss on postpartum performance and health outcomes in dairy cattle.